2024
DOI: 10.1038/s41467-023-44313-9
|View full text |Cite
|
Sign up to set email alerts
|

Serglycin secreted by late-stage nucleus pulposus cells is a biomarker of intervertebral disc degeneration

Fan Chen,
Linchuan Lei,
Shunlun Chen
et al.

Abstract: Intervertebral disc degeneration is a natural process during aging and a leading cause of lower back pain. Here, we generate a comprehensive atlas of nucleus pulposus cells using single-cell RNA-seq analysis of human nucleus pulposus tissues (three males and four females, age 41.14 ± 18.01 years). We identify fibrotic late-stage nucleus pulposus cells characterized by upregulation of serglycin expression which facilitate the local inflammatory response by promoting the infiltration of inflammatory cytokines an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…It offers insights into physiological and pathological processes and has been increasingly applied in IVD research. Several studies have identified novel phenotypic biomarkers of NP cells, significantly enhancing our understanding of NP cell biology and development ( Fernandes et al, 2020 ; Ling et al, 2021 ; Panebianco et al, 2021 ; Zhang et al, 2021 ; Cherif et al, 2022 ; Han et al, 2022 ; RNA, 2022 ; Guo et al, 2023a ; Chen et al, 2024 ). However, the heterogeneity of IVDD among young and elderly individuals remains to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…It offers insights into physiological and pathological processes and has been increasingly applied in IVD research. Several studies have identified novel phenotypic biomarkers of NP cells, significantly enhancing our understanding of NP cell biology and development ( Fernandes et al, 2020 ; Ling et al, 2021 ; Panebianco et al, 2021 ; Zhang et al, 2021 ; Cherif et al, 2022 ; Han et al, 2022 ; RNA, 2022 ; Guo et al, 2023a ; Chen et al, 2024 ). However, the heterogeneity of IVDD among young and elderly individuals remains to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%